Desidratação osmótica de figo (Ficus carica L.) verde cultivado no sudoeste de Minas Gerais - Mello Júnior, Ronaldo Elias de (2016)
The aim of this work was the study of osmotic dehydration of green figs cuted crosswise, using sucrose with and without vacuum pulse. Figs, in sucrose solutions at concentrations of 40, 50 and 60 ° Brix at 40 ° C, with vacuum pulse application (74 mm Hg) during the first 5 minutes in total time of 240 minutes, initially, obtained osmotic dehydration kinetic curves with pulsed vacuum (PVOD). It was tested the fit of models Azuara and Peleg. It were observed higher losses of water and solids gain and smaller fruit water activity values with increasing concentration. The tested models showed good fits, and the Azuara led to closer to actual values. In a second step, the PVOD were studied according to a central composite rotational design (CCRD). Was set up a full factorial 2³ with 6 axial points and four central points, making 18 experiments. The factors investigated were the temperature (31.6 to 48.4 ° C), the concentration of the dehydrating solution (46.59 to 63,41ºBrix) and vacuum pulse time (0 to 40 minutes). The variance analysis evaluated the influence of temperature on the reduction of the moisture content and in increasing the soluble solid content of osmotically dehydrated samples. In order to find the operating conditions capable of providing lower moisture and higher soluble solids, temperature range from 35 ° C with a concentration of 60 ° Brix by vacuum pulse application during 32 min proved capable of meeting the requirements, providing fruit with a moisture content of 72.83% (wb) and soluble solids content of 18.61 ° Brix.